2007
DOI: 10.1063/1.2738376
|View full text |Cite
|
Sign up to set email alerts
|

Thermal loading of laser induced plasma shockwaves on thin films in nanoparticle removal

Abstract: Damage concerns, such as substrate/film material alterations, damage, and delamination of thin films, have become a central problem in sub-100 nm particle removal applications. In the laser induced plasma (LIP) removal technique both LIP shockwave and radiation heating are potential sources of thermomechanical damage. The specific objective of current study is to conduct a computational investigation of the LIP shockwave effect on the thermoelastic response of a thin chromium (Cr) film deposited on a quartz su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…1 for the experimental setup). Various shockwave characteristics [29]- [33] (the location of the shockwave front as a function of the arrival time) along with the obtained experimental results compared in [18] indicate slight offsets due to the different laser pulse energies utilized.…”
Section: Lip Removal Techniquementioning
confidence: 98%
See 1 more Smart Citation
“…1 for the experimental setup). Various shockwave characteristics [29]- [33] (the location of the shockwave front as a function of the arrival time) along with the obtained experimental results compared in [18] indicate slight offsets due to the different laser pulse energies utilized.…”
Section: Lip Removal Techniquementioning
confidence: 98%
“…1. A dynamic pressure transducer [27], [28] with a resonant frequency of 500 kHz (i.e., a rise time of 1 s), a surface diameter of 5.54 mm (Kistler 603B1), and a Spectra Physics Nd:YAG INDI-series pulsed-laser (450 mJ rated pulse energy, 5-8 ns pulse width, 10 Hz repetitive rate, 8.5-10 mm beam diameter, and 1064 nm wavelength) were utilized for the transient pressure measurement experiments [29] (see inset of Fig. 1 for the experimental setup).…”
Section: Lip Removal Techniquementioning
confidence: 99%
“…From the results of the previous FE simulations it can be concluded that the surface stresses induced due to surface temperature were dominating the stresses induced due to shock pressure loading. However, the induced stresses, radial (a peak level of approximately 650 MPa), shear ( 120 kPa), and axial ( 200 kPa) stress components with both thermal and mechanical loadings, were within the damage limits of the material when the effect of the level of dynamic strain rate is taken into consideration [7]. It is then concluded that the substrate damage could be caused by the radiation heating generated by the LIP.…”
Section: Introductionmentioning
confidence: 97%
“…The pressure levels are typically too low to result in any mechanical substrate damage, as the strength of the substrate is often three orders of magnitude higher than the shock pressure. The effect of shock temperature and pressure on a film bonded to a substrate is determined by a computational analysis based on the finite-element (FE) method and it is reported in [6] and [7]. From the results of the previous FE simulations it can be concluded that the surface stresses induced due to surface temperature were dominating the stresses induced due to shock pressure loading.…”
Section: Introductionmentioning
confidence: 98%
“…The radial stress is long-ranged and simply inversely proportional to the distance r. The manner definitely changes when the surrounding medium is supercooled liquids or solids. Laser-induced thermal stresses on nanoparticle removal from thin films 32) and due to metal nanoparticles in silica matrices 33) are compelling evidence.…”
Section: Thermal Strain Of Ag@fe 3 O 4 Nanoflowersmentioning
confidence: 99%